Case Report: Early Transcontinental Import of SARS-CoV-2 Variant of Concern 202012/01 (B.1.1.7) From Europe to Uruguay - Salazar, Cecilia; Costabile, Alicia; Ferrés, Ignacio; Perbolianachis, Paula; Pereira-Gómez, Marianoel; Simón, Diego; Galiana, Antonio; Pi, Beatriz; Antelo, Virginia; García, Rosario; Moreno, Pilar; Moratorio, Gonzalo; et al. (Frontiers in Virology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variant B.1.1.7 causes a more transmissible and apparently more severe disease. We report its early introduction from Europe to South America from a traveler who arrived in Uruguay from the United Kingdom, even before B.1.1.7 was recognized as a variant of concern. This highlights the risk of introduction of SARS-CoV-2 variants despite strict contingency protocols and underscores the need of improving real-time surveillance worldwide.